(untitled) (Movimenta (ISSN 1984-4298), 2023)
Cerebral Palsy (CP) is the most common physical disability in childhood and is associated with sensory alterations and cognitive limitations. Early diagnosis is crucial, based on a specific assessment, with a view to appropriate intervention that promotes motor and cognitive gains during a period of great neural plasticity. To this end, identifying risk factors for the development of CP is essential. Aim: to assess and detect the risk of CP in babies discharged from the NICU. Method: cross-sectional study with 35 babies who were assessed using the HINE neurological assessment. Results: 68.6% of the sample was male, 85.7% were premature, 54.3% had low birth weight. Cesarean delivery was the most prevalent (68.6%), and 31.4% of the sample were identified as being at risk of CP in the standardized neurological examination. Specifically, all the babies at risk were premature, 81.8% were male and 45.5% had a low birth weight. Conclusion: Babies coming out of the NICU are more likely to have unfavorable developmental outcomes, and the risk of developing CP can be identified early when neurological examination, MRI and HINE assessment are combined